2011
DOI: 10.1016/j.pain.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Intraepidermal nerve fiber loss corresponds to the development of Taxol-induced hyperalgesia and can be prevented by treatment with minocycline

Abstract: Loss of intraepidermal nerve fibers (IENFs) has been speculated to play a critical role in the development of various neuropathies. In this study, the density of IENFs were studied over time during the induction of Taxol-induced chemoneuropathy and compared with the changes in IENFs in animals co-treated with Taxol plus the protective agent minocycline. Rats were injected (i.p.) with 2mg/kg of Taxol every other day for 4 injections (Days 1, 3, 5, and 7). Minocycline (25 mg/kg) was given in a separate group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
192
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(216 citation statements)
references
References 48 publications
18
192
0
2
Order By: Relevance
“…It has been reported in several studies that paclitaxel is responsible for the development of peripheral neuropathic pain by increasing proinflammatory IL-1β expression (8)(9)(10)(11)(12). The IL-1β gene expression level increased in the paclitaxel group (PAC) compared to that in the HG and decreased in the groups in which anakinra was administered.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported in several studies that paclitaxel is responsible for the development of peripheral neuropathic pain by increasing proinflammatory IL-1β expression (8)(9)(10)(11)(12). The IL-1β gene expression level increased in the paclitaxel group (PAC) compared to that in the HG and decreased in the groups in which anakinra was administered.…”
Section: Discussionmentioning
confidence: 98%
“…It has been found in numerous studies that reactive oxygen species (ROS) cause nerve injury-related pain and inflammatory pain (7). Paclitaxel has also been reported to activate proinflammatory cytokine expression (8)(9)(10)(11). Thus, the administration of paclitaxel results in the production of interleukin-1 beta (IL-1β) and other proinflammatory cytokines and their release from microglial cells.…”
mentioning
confidence: 99%
“…A preclinical study of BCP indicated that the drug only attenuated pain behavior at an early stage (from d 4 to d 6) by inhibiting microglia [44] ; however, an increasing number of therapeutic effects of the agent have been identified. In studies of CIPN, minocycline prevented CIPN-related symptoms and the activation of astrocytes despite the lack of microglial activation indicators [16][17][18][19] . Nevertheless, minocycline also possesses neuroprotective roles [20,28,45,46] .…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…Minocycline, a second generation tetracycline antibiotic, selectively inhibits microglia. However, accumulating evidence indicates that it prevents chemotherapy-induced peripheral neuropathy (CIPN) via the inhibition of astrocytes [16][17][18][19] . Moreover, it has also been demonstrated that minocycline down-regulates NF-κB activity in several other cell lines [20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…15 Because motor and sensory functions are often affected in a heterogeneous pattern, these agents appear to harm different types of neurons and in particular their axons (axonopathy) in humans with chemotherapy-induced PN 16,17 and in rodent models. 18 Moreover, as with DM-associated PN, the longest axons in the body appear to be preferentially vulnerable, and this may be due to their enhanced energy demand for transporting cellular constituents within long axons. Indeed, for >30 years axon transport abnormalities were recognized to have a role in PN caused by DM.…”
Section: Axon Transport and Its Role In Neuron And Axon Homeostasismentioning
confidence: 99%